Seleção de Bacillus thuringiensis Berliner e Trichogramma pretiosum Riley (Hymenoptera:trichogrammatidae) para Spodoptera frugiperda (J. E. Smith) (Lepidoptera: Noctuidae) e suas interações - Ferreira, Lígia Souza (2010)
The increasing number of corn production areas and the different amount of working strategies used to grow it have increased the number of pests. The monoculture strategy and the frequent use of insecticides expose this culture to severe attacks of severa